Using a representative sample to estimate the number of martyrs in Russia in the 20th century - Nikolay Somin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
This article proposes a method for estimating the number of martyrs in the Russian Orthodox Church from repressions of the 20th century in Russia. The method is based on the well-known formula of multiplication of independent events. If in this formula the probabilities are replaced with their statistical counterparts, it will be possible to obtain a ratio for calculating the total number of victims (N) through the known or calculated parameters. For a computer experiment, two databases containing the information about martyrs have been taken: the database “Martyrs for Christ”, developed at St. Tikhon’s Orthodox University for the Humanities, and an electronically compiled list of believers from the database made by “Memorial” society. The article shows that, as a fi rst approximation, these bases are independent, as the range of estimates of the main subsets has not exceeded 50%, and therefore the use of the theorem of multiplication of probabilities will not lead to bad mistakes. To carry out a computer experiment (in C language), a programming complex has been developed which processes both databases and establishes their overlapping. As a result of the experiment, the estimation of 109,756 persons has been obtained. Estimations of martyrs in the main subsets have also been made: monks 13,499 persons, priests 40,938 persons, deacons and psalm readers 8,451 persons, sextons and members of “the twenties” 12,951 persons, other lay people 33,914 persons. In order to obtain the estimations in the subsets, the list of victims of Ulyanovskaya Diocese was used; it was compiled based on the book Church in Chains (Russ. Церковь в узах) by archpriest Alexy Skala, which is particularly full. The numbers of the victims accord well with the documentary testimonies (Ezhov’s letter to Stalin) and with previous articles by the author. The results show that the scale of the persecutions is in fact not as large as it had been believed earlier.